How I use platelet transfusions - Stanworth, Simon J; Shah, Akshay (Blood, 2022)
Platelet transfusions are commonly administered for the prevention or treatment of bleeding in patients with acquired thrombocytopenia across a range of clinical contexts. Recent data, including randomized trials, have highlighted uncertainties in the risk-benefit balance of this therapy, which is the subject of this review. Hemovigilance systems report that platelets are the most frequently implicated component in transfusion reactions. There is considerable variation in platelet count increment after platelet transfusion, and limited evidence of efficacy for clinical outcomes, including prevention of bleeding. Bleeding events commonly occur despite the different policies for platelet transfusion prophylaxis. The underlying mechanisms of harm reported in randomized trials may be related to the role of platelets beyond hemostasis, including mediating inflammation. Research supports the implementation of a restrictive platelet transfusion policy. Research is needed to better understand the impact of platelet donation characteristics on outcomes, and to determine the optimal thresholds for platelet transfusion before invasive procedures or major surgery (eg, laparotomy). Platelet transfusion policies should move toward a risk-adapted approach that does not focus solely on platelet count.